BMI z‐Scores are a poor indicator of adiposity among 2‐ to 19‐year‐olds with very high BMIs, NHANES 1999‐2000 to 2013‐2014. Issue 4 (28th February 2017) - Freedman, David S.; Butte, Nancy F.; Taveras, Elsie M.; Lundeen, Elizabeth A.; Blanck, Heidi M.; Goodman, Alyson B.; Ogden, Cynthia L.
Abstract : Objective: Although the Centers for Disease Control and Prevention (CDC) growth charts are widely used, BMI‐for‐age z ‐Scores (BMIz) are known to be uninformative above the 97th percentile. This study compared the relations of BMIz and other BMI metrics (%BMIp95, percent of 95th percentile, and ΔBMIp95, BMI minus 95th percentile) to circumferences, skinfolds, and fat mass. We were particularly interested in the differences among children with severe obesity (%BMIp95  ≥ 120). Methods: Data was used from 30, 003 2‐ to 19‐year‐olds who were examined from 1999‐2000 through 2013‐2014 in the National Health and Nutrition Examination Survey (NHANES). Results: The theoretical maximum BMIz based on the growth charts varied by more than threefold across ages. The BMI metrics were strongly intercorrelated, but BMIz was less strongly related to the adiposity measures than were ΔBMIp95 and %BMIp95 . Among children with severe obesity, circumferences and triceps skinfold showed almost no association with BMIz ( r  ≤ 0.10), whereas associations with %BMIp95 and ΔBMIp95 ranged from r  = 0.32 to 0.79. Corresponding associations with fat mass ÷ height 2 ranged from r  = 0.40 (BMIz) to r =0.82 (%BMIp95 ) among 8‐ to 19‐year‐olds. Conclusions: Among children with severe obesity, BMIz is only weakly associated with other measures of body fatness. Very high BMIs should be expressed relative to the CDC 95th percentile, particularly in studies that evaluate obesity interventions.